Using Murine Models to Investigate Tumor–Lymphoid Interactions: Spotlight on Chronic Lymphocytic Leukemia and Angioimmunoblastic T-Cell Lymphoma - Herek, Tyler A.; Cutucache, Christine E. (Frontiers in Oncology, 2017)
The role of the tumor microenvironment in leukemias and lymphomas is well established, yet the intricacies of how the malignant cells regulate and influence their non-malignant counterparts remain elusive. For example, chronic lymphocytic leukemia (CLL) is an expansion of malignant CD5+CD19+ B cells, yet the non-malignant T cells play just as large of a role in disease presentation and etiology. Herein, we review the dynamic tumor cell to lymphoid repertoire interactions found in two non-Hodgkin’s lymphoma subtypes: CLL and angioimmunoblastic T-cell lymphoma. We aim to highlight the pivot work done in the murine models which recapitulate these diseases and explore the insights that can be gained from studying the immuno-oncological regulation of non-malignant lymphoid counterparts.